Lodging Rice Resistant : Identification on MorphoPhysiological Paddy Stems Falling Factor in Different Planting Methods - Syahrullah Syahrullah; Rosmaladewi Rosmaladewi; Sulfiani Sulfiani; Erni Kasim (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2022)
Due to the extreme weather that hit throughout the year resulted in the threat of rice plants falling down. It was known that the fall of rice plants was a limiting factor for obtaining high yields and quality of grain. Therefore, it was considered important to evaluate the resistance to fall in the general methods of planting rice in the area. Those were transplanting planting (TP) and direct seed planting (TBL). Based on this objective, we identified the morphophysiology of rice stems in the laying factor of 2 planting methods commonly used by farming communities, namely transplanting planting and direct seed planting. Identification was carried out by observing the morphology and physiology of the rice stalks, the laying index and the level of fall of rice plants in each planting method (TP and TBL). The result of the research was that the direct seed planting method (TBL) tends to show morphophysiological identification results that were not resistant to falling compared to the transplanting method (TP). The laying rate shown by TBL was accounting for 75.5% while transplanting (TP) was only 5.7% of the experimental unit area. Significant differences were observed in plant height, stem length, center of gravity height, laying index, laying level, stem internode length, stem internode width, bending moment and bending stress of the stem. In the experiment, it was also found that the grain was damaged due to the fall of the rice plant when the rice fields were flooded. Therefore, it is important to carry out agronomic management as part of sustainable mitigation of the risk of falling rice plants to support national food security